Monitoring global protein thiol-oxidation and protein S- mycothiolation in Mycobacterium smegmatis under hypochlorite stress - Hillion, Melanie; Wirtz, Markus; Hell, Rüdiger (Scientific reports, 2017)
Mycothiol (MSH) is the major low molecular weight (LMW) thiol in Actinomycetes. Here, we used shotgun proteomics, OxICAT and RNA-seq transcriptomics to analyse protein S-mycothiolation, reversible thiol-oxidations and their impact on gene expression in Mycobacterium smegmatis under hypochlorite stress. In total, 58 S-mycothiolated proteins were identified under NaOCl stress that are involved in energy metabolism, fatty acid and mycolic acid biosynthesis, protein translation, redox regulation and detoxification. Protein S-mycothiolation was accompanied by MSH depletion in the thiol-metabolome. Quantification of the redox state of 1098 Cys residues using OxICAT revealed that 381 Cys residues (33.6%) showed >10% increased oxidations under NaOCl stress, which overlapped with 40 S-mycothiolated Cys-peptides. The absence of MSH resulted in a higher basal oxidation level of 338 Cys residues (41.1%). The RseA and RshA anti-sigma factors and the Zur and NrdR repressors were identified as NaOCl-sensitive proteins and their oxidation resulted in an up-regulation of the SigH, SigE, Zur and NrdR regulons in the RNA-seq transcriptome. In conclusion, we show here that NaOCl stress causes widespread thiol-oxidation including protein S-mycothiolation resulting in induction of antioxidant defense mechanisms in M. smegmatis. Our results further reveal that MSH is important to maintain the reduced state of protein thiols.